2022
DOI: 10.1017/flo.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Plate lines to enhance wake vortex decay for reduced separations between landing aircraft

Abstract: To mitigate the risk of wake vortex encounters during final approach, so-called plate lines have been developed. Data collected during a six-month measurement campaign at Vienna International Airport are used to assess the potential for reducing minimum aircraft separations facilitated by plate lines during approach and landing following the re-categorisation (RECAT-EU) methodology for revised wake turbulence categorisation. To ensure that no other parameters controlling wake vortex decay bias the analysis, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…For some aircraft pairings, even higher bene ts of more than 1 NM or 20% seem to be possible with Plate Lines. Landing aircraft with Plate Line at Vienna International Airport Figure 3 P2P prediction of circulation evolution for a number of heavy aircraft types under reasonable worst-case conditions Figure 4 The generic reasonable worst-case decay curves with and without Plate Line and the reference generic decay curve from RECAT-EU [12] Figure 5 Absolute reduction of minimum separations due to the Plate Line based on RECAT-EU-PWS seperations (IGE consideration only) [11] Figure 6 Percental reduction of minimum separations due to the Plate Line based on RECAT-EU-PWS seperations (IGE consideration only) [11] Figure 7 Separations and RMCs for the Learjet 35 as an exemplary follower aircraft Figure 8 Results of the combined analysis for IGE-PL and OGE when using RECAT-EU-PWS as reference (absolute values) Figure 9 Results of the combined analysis for IGE-PL and OGE when using RECAT-EU-PWS as reference (percental values)…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For some aircraft pairings, even higher bene ts of more than 1 NM or 20% seem to be possible with Plate Lines. Landing aircraft with Plate Line at Vienna International Airport Figure 3 P2P prediction of circulation evolution for a number of heavy aircraft types under reasonable worst-case conditions Figure 4 The generic reasonable worst-case decay curves with and without Plate Line and the reference generic decay curve from RECAT-EU [12] Figure 5 Absolute reduction of minimum separations due to the Plate Line based on RECAT-EU-PWS seperations (IGE consideration only) [11] Figure 6 Percental reduction of minimum separations due to the Plate Line based on RECAT-EU-PWS seperations (IGE consideration only) [11] Figure 7 Separations and RMCs for the Learjet 35 as an exemplary follower aircraft Figure 8 Results of the combined analysis for IGE-PL and OGE when using RECAT-EU-PWS as reference (absolute values) Figure 9 Results of the combined analysis for IGE-PL and OGE when using RECAT-EU-PWS as reference (percental values)…”
Section: Discussionmentioning
confidence: 99%
“…The results of that previous study shall only be recapitulated as far as required to understand the combined analysis in and out of ground effect as presented in section 3. Details on the previous study can be found in references [11] and [12].…”
Section: Models and Measurementsmentioning
confidence: 99%
See 3 more Smart Citations